(untitled) (Journal of Parents and Teachers, 2014)
Ethics is an essential foundation for human coexistence and encompasses respect for the individual, both his dignity and his inviolable rights. However, within ethics there are a series of rules that regulate coexistence and these can be classified into two groups, "maximums" and "minimums". The "maximums" are those that indicate the path to follow once we have individually chosen the path of our existence. On the other hand, the "minimums" refer to those that guarantee respect for essential rights such as, for example, the right to food and health, as well as the right to think and speak.